The scientific periodical production affiliated to the National Institute of the Atlantic Forest (INMA) at Scopus database (2009-2018) - Lazzarotto Freitas, Juliana; Rosas, Fabio Sampaio [UNESP]; Mendes, Sergio Lucena (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2020)
Introduction: this study considers as object of analysis the scientific articles production affiliated to the National institute of the Atlantic Forest (INMA). It aims to recognize visibility, impact, thematic and collaborative relationships established by researchers afilliated to the Institute over ten years (2009-2018). It starts from the scientific question: how is this scientific production configured regarding priority thematic areas, journals, authors, institutions and most productive countries, and what is its impact on the citations received? Method: it adopts the metric studies of information as methodology, identifying a corpus of 73 articles linked to INMA by the institutional affiliation of its researchers over a period of ten years. It uses the Scopus database to identify this production and also the Scival database as an instrument to generate indicators. Results: it points out that the production affiliated to INMA has high internationalization rates, as it is published in 72% of international journals. In addition, the corpus receives a high average of citations (4.22 citations per article). The articles with the highest number of citations have greater impact than the average citations of the journals in which they are published. Interinstitutional relations and between authors are built in line with the thematic and historical scope of the institute, consolidating areas and research trends on zoology and botany. Conclusion: the profile of the scientific production portrayed contributes as a strategic element for the consolidation of INMA's research memory.
Keywords: National Institute of the Atlantic Forest; Scientific production analysis; Metric Studies of information; Scientific Visibility; Scientific Impact; Scientific Collaboration